Public health informatics specialists in state and local public health workforce: insights from public health workforce interests and needs survey - Rajamani, Sripriya; Leider, Jonathon P; Gunashekar, Divya Rupini; Dixon, Brian E (Journal of the American Medical Informatics Association : JAMIA, 2025)
Modernizing and strengthening the US public health data and information infrastructure requires a strong public health informatics (PHI) workforce. The study objectives were to characterize existing PHI specialists and assess informatics-related training needs. To examine the PHI workforce, the 2021 Public Health Workforce Interests and Needs Survey (PH WINS), a nationally representative survey with 44 732 governmental public health (PH) respondents was analyzed. The survey included data from 47 state health agencies-central office, 29 large local health departments (Big Cities Health Coalition members), and 259 other local/regional health departments. Analysis focused on "public health informatics specialist" (PHI), "information system manager/information technology specialist" (IT/IS), "public health science" (PHS), and "clinical and laboratory" (CL) roles. PHI specialists account for less than 2% of the governmental PH workforce. A majority were female (68%), White (55%), and close to half in 31-50 age category (49%). Most (74%) were in non-supervisory roles and <1% in managerial/executive roles, with less than one-third (29%) earning >$75 000 salary. Skill gaps on informatics-related tasks included: identify appropriate data/information sources; collect valid data for decision making; participate in quality improvement processes; identify evidence-based approaches. The PHI specialists reported lower skill gaps in data/informatics areas when compared to other public health roles (PHS and CL), and this was consistent across state/local settings. Given the scale of work needed for modernization of information systems, PH agencies need more individuals in informatics roles. To attract PHI specialists, better salaries, clear PHI job classifications and permanent PHI workers are needed, which requires sustained investments from federal and state governments. Efforts to train PHI specialists, recruit and retain them in the governmental public health workforce, and address hiring issues in public health agencies are essential next steps to transform the US public health enterprise.